An assessment of baseline and downscaled projected climate variables in the Upper Manyame sub-catchment of Zimbabwe. (December 2019) - Masimba, Oliver; Gumindoga, Webster; Mhizha, Alexander; Rwasoka, Donald Tendayi
Abstract: The study assessed historical trends in precipitation and temperature using Mann-Kendall trend and Wilcoxon signed rank tests in the Upper Manyame sub-catchment of Zimbabwe. The projected precipitation and temperature for the 2030s and 2060s were downscaled using the Statistical DownScaling Model with data from HadCM3 and CanESM2. Trend analysis results showed a declining statistically non-significant trend in precipitation and a statistically significant rising trend in maximum and minimum temperature. The projected temperature analysis through the A2a and B2a scenarios showed that the maximum temperature will increase by 0.39 °C and 0.35 °C for the 2030s and 0.64 °C and 0.51 °C for the 2060s respectively whilst the minimum temperature will increase by 0.15 °C and 0.11 °C for the 2030s and 0.25 °C and 0.2 °C for the 2060s respectively. The downscaled CanESM2 data showed that maximum and minimum temperature will increase by 0.5 °C–0.9 °C and 0.3 °C–0.8 °C respectively for RCP2.6 and RCP8.5. Monthly projections for HadCM3 in both the 2030s and 2060s, revealed that the amount of precipitation will decrease in January, March and October and generally increase in February, November and December. There will be a 20-40% decline in precipitation for RCP2.6, and 50% for RCP8.5. The results are very important for climate proofing systems. Highlights: Trend analysis of historical data was done using Mann-Kendall trend and Wilcoxon signed rank tests. Statistical DownScaling Model was used for downscaling the projected precipitation and temperature. Data from HadCM3 and CanESM2 was used. Results were analyzed against the baseline data.